Facilitating Information Sharing Across the International Space Community Lessons from Behavioral Science - Keller, Kirsten M. (RAND Corporation, 2013)
Space debris is a growing threat that will increasingly affect future space-related missions. The space community would benefit from sharing information, but its members are not always willing to do so. This report examines some of the potential behavioral and psychological barriers that may prevent information sharing and suggests ways the U.S. Air Force might be able to facilitate improved information sharing among space-faring entities.